2001
DOI: 10.1029/2000gl012118
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐dependent attenuation in the uppermost inner core from the Taiwan short period seismic array PKP data

Abstract: Abstract. Inner core attenuation properties from two spots were examined in detail using PKIKP and PKP(BC) phases with a distance range of between 147 ø and 154 ø as recorded by both the short-period regional seismic array in Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The various studies come to a general agreement about low Q in the uppermost inner core, with values ranging from 100 to 400 in the uppermost 200 km, probably increasing with depth up to 600 at 400 km (Doornbos, 1974(Doornbos, , 1983Bolt, 1977;Cormier, 1981;Niazi and Johnson, 1992;Bhattacharyya et al, 1993;Souriau and Roudil, 1995;Tseng et al, 2001;Oreshin and Vinnik, 2004). Waveform modeling of PKP at nearly antipodal distances also shows a Q-increase at radius smaller than 500 km, together with a decrease in the scatter of the Q-values .…”
Section: The Apparent Incompatibility Of Body Wave and Normal Mode Rementioning
confidence: 72%
See 1 more Smart Citation
“…The various studies come to a general agreement about low Q in the uppermost inner core, with values ranging from 100 to 400 in the uppermost 200 km, probably increasing with depth up to 600 at 400 km (Doornbos, 1974(Doornbos, , 1983Bolt, 1977;Cormier, 1981;Niazi and Johnson, 1992;Bhattacharyya et al, 1993;Souriau and Roudil, 1995;Tseng et al, 2001;Oreshin and Vinnik, 2004). Waveform modeling of PKP at nearly antipodal distances also shows a Q-increase at radius smaller than 500 km, together with a decrease in the scatter of the Q-values .…”
Section: The Apparent Incompatibility Of Body Wave and Normal Mode Rementioning
confidence: 72%
“…This central, high-Q zone corresponds approximately to the innermost inner core identified by Ishii et al (2002b) and Beghein and Trampert (2003) (Figure 14), and could correspond to a different fabric (Cormier and Stroujkova, 2005). Largescale regional variations of Q seem to be present, with a hemispherical pattern correlated to the one observed at greater depth (Tseng et al, 2001;Wen and Niu, 2002;Cao and Romanowicz, 2004b;Yu and Wen, 2006a). Largescale regional variations of Q seem to be present, with a hemispherical pattern correlated to the one observed at greater depth (Tseng et al, 2001;Wen and Niu, 2002;Cao and Romanowicz, 2004b;Yu and Wen, 2006a).…”
Section: The Apparent Incompatibility Of Body Wave and Normal Mode Rementioning
confidence: 81%
“…From early on, measurements of amplitude ratios of PKP(DF) (sampling the inner core) and PKP(BC) (sampling the outer core) constrained Q a in the top 500 km of the inner core to be in the range 200-600 (e.g., Bhattacharyya et al, 1993;Bolt, 1977;Choy and Cormier, 1983;Cormier, 1981;Doornbos, 1974Doornbos, , 1983Ivan et al, 2005;Niazi and Johnson, 1992;Sacks, 1969;Song and Helmberger, 1993;Tseng et al, 2001). Most studies have suggested an increase of Q a with depth, although some find that Q a is constant with depth (e.g., Bhattacharyya et al, 1993;Niazi and Johnson, 1992).…”
Section: Attenuation In the Inner Corementioning
confidence: 99%
“…Large deep events at a distance greater than 140°from South America are well recorded on the IESAS continuous data string. These seismic core phases have been employed to study the structure of the Earth's core (Tseng et al, 2001) and the rupture mechanisms of deep earthquakes (Huang, 2002).…”
Section: Datamentioning
confidence: 99%